Peran Profitabilitas Guna Memperkuat Corporate Social Responsibility Disclosure - Raissya Rahma Amelia; Syamsul Bahri Arifin; Rizki Filhayati Rambe (Pusat Riset Manajemen Dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia, 2022)
The purpose of this study was to determine the effect of leverage, firm size, liquidity on corporate social responsibility disclosure with profitability as a moderating variable. The approach used in this research is a quantitative approach. The population in this study were all manufacturing companies listed on the Indonesia Stock Exchange. The sample in this study used purposive sampling totaling 52 companies. Data collection techniques in this study using documentation techniques. The data analysis technique in this study used descriptive statistical tests, classical assumption tests, moderated regression analysis, model feasibility tests, and hypothesis testing. The results of this study prove that partially leverage, firm size and liquidity have an effect on corporate social responsibility disclosure. The results of moderating regression analysis with residual equations show that profitability cannot moderate the effect of leverage, firm size and liquidity on corporate social responsibility disclosure in manufacturing companies listed in Indonesia Stock Exchange 2016-2020.